2020
DOI: 10.5194/hess-24-4369-2020
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a prolonged meteorological drought on catchment water storage capacity: a hydrological-model perspective

Abstract: Abstract. Understanding the propagation of prolonged meteorological drought helps solve the problem of intensified water scarcity around the world. Most of the existing literature studied the propagation of drought from one type to another (e.g., from meteorological to hydrological drought) with statistical approaches; there remains difficulty in revealing the causality between meteorological drought and potential changes in the catchment water storage capacity (CWSC). This study aims to identify the response … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…The original GR4J model framework proposed by Perrin et al (2003) parameter θ1 and its time-varying characteristics are used to represent the change of real CWSC. It is noted that θ2, θ3 and θ4 are assumed to remain constant, similar settings can be found in many previous studies (Westra et al, 2014;Pan et al, 2020).…”
Section: Model Structurementioning
confidence: 61%
See 2 more Smart Citations
“…The original GR4J model framework proposed by Perrin et al (2003) parameter θ1 and its time-varying characteristics are used to represent the change of real CWSC. It is noted that θ2, θ3 and θ4 are assumed to remain constant, similar settings can be found in many previous studies (Westra et al, 2014;Pan et al, 2020).…”
Section: Model Structurementioning
confidence: 61%
“…Shen et al (2018) Many previous literatures (McNamara et al, 2011;Melsen et al, 2016;Carrer et al, 2019) influence the mechanism of hydrological response of catchments. Our previous study (Pan et al, 2020) has showed that significant shift in the CWSC has been identified in almost two thirds of the catchments in south-eastern Australia during the prolonged meteorological drought period compared with the previous non-drought period, which may result in the opposite response in two subsets of catchments, i.e., runoff generation rates of some catchments were lower while others had higher runoff generation rate.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A large number of studies have been presented to assess the hydrological response to climate change or anthropic intervention at different scales with the purpose to formulate adaptive water resources planning and allocation strategies for the future 17 , 19 21 . For example, Chawla and Mujumdar 20 examined the runoff response in the upper Ganga basin with the VIC model and illustrated that the runoff is sensitive to the change of urban areas and climate change.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chawla and Mujumdar 20 examined the runoff response in the upper Ganga basin with the VIC model and illustrated that the runoff is sensitive to the change of urban areas and climate change. Pan et al 21 studied the hydrological response of 83 catchments in southeastern Australia before and during the meteorological drought period based on the GR4J model, and significant shifts in the catchment water storage capacity have been observed in 62.7% of the meteorological drought period. Yin et al 17 studied the temperature scaling of precipitation and storm runoff extremes under different climate conditions over mainland China.…”
Section: Introductionmentioning
confidence: 99%